2015
DOI: 10.5140/jass.2015.32.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Comparison of Gravity Wave Characteristics Obtained from Airglow All-Sky Observation at Mt. Bohyun, Korea and Shigaraki, Japan

Abstract: Previously, all-sky airglow images observed at Shigaraki (34.9° N, 136.1° E), Japan, during 2004 and2005 were analyzed in relation to those observed at Mt. Bohyun (36.2° N, 128.9° E) for a comparison of their gravity wave characteristics (Kim et al. 2010). By applying the same selection criteria of waves and cloud coverages as in the case of Mt. Bohyun all-sky images, we derived apparent wavelengths, periods, phase velocities, and monthly occurrence rates of gravity waves at Shigaraki in this study. The distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Previous studies of mid-latitude gravity waves have reported that gravity waves in eastward and northward propagations dominate most of the summer (Taylor et al, 1993;Nakamura et al, 1999;Walterscheid et al, 1999;Hecht et al, 2001;Ejiri et al, 2003;Tang et al, 2005). Observations at BHO have confirmed the similar tendency of propagation in summer Yang et al, 2015). The summer bias of wave propagation can be distinctly due to the criticallevel filtering by the prevailing zonal and meridional winds in the lower atmosphere.…”
Section: Characteristics Of Observed Waves At Mt Bohyunsupporting
confidence: 56%
See 2 more Smart Citations
“…Previous studies of mid-latitude gravity waves have reported that gravity waves in eastward and northward propagations dominate most of the summer (Taylor et al, 1993;Nakamura et al, 1999;Walterscheid et al, 1999;Hecht et al, 2001;Ejiri et al, 2003;Tang et al, 2005). Observations at BHO have confirmed the similar tendency of propagation in summer Yang et al, 2015). The summer bias of wave propagation can be distinctly due to the criticallevel filtering by the prevailing zonal and meridional winds in the lower atmosphere.…”
Section: Characteristics Of Observed Waves At Mt Bohyunsupporting
confidence: 56%
“…All-sky images were obtained with 4 × 4 binning to increase signal-to-noise ratios. A detailed description of the all-sky camera at BHO is given in Yang et al (2015). The OI 557.7 nm filter has a central wavelength of 557.81 nm with a full width at half maximum of 1.53 nm.…”
Section: Observational and Model Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies for mid-latitude gravity waves have reported in the majority the dominance of eastward and northward propagations during summer (Taylor et al, 1993;Nakamura et al, 1999;Walterscheid et al, 1999;Hecht et al, 2001;Ejiri et al, 2003;Tang et al, 2005). Observations at BHO have confirmed the similar tendency of propagation in summer Yang et al, 2015). The summer bias of wave propagation can be distinctly due to the critical level filtering by the prevailing zonal and meridional winds in the lower atmosphere.…”
Section: Characteristics Of Observed Waves At Mt Bohyunsupporting
confidence: 56%
“…camera at BHO is an ultra-high speed (f/0.95) 3-inch camera composed of a fisheye lens with a viewing angle of 180°, telecentric lens to adjust airglow emission light path for parallel incident to filter, a 6-position filter wheel installed with two narrowband filters (OI-557.7, OI-630.0), and a 1024×1025 CCD detector. The detail description of the all-sky camera at BHO has been given in Yang et al (2015). The images with the OI 557.7 filter were obtained continuously at intervals of 5 minute with an exposure time of 90-150 seconds and a spatial resolution of 500 km radial region.…”
Section: Observational and Model Datamentioning
confidence: 99%